Adult human nasal mesenchymal stem cells have an unexpected broad anatomic distribution. Issue 7 (19th February 2013) - Goldstein, Bradley J.; Hare, Joshua M.; Lieberman, Seth; Casiano, Roy
Abstract : Background: The olfactory epithelium is a self‐renewing tissue, able to produce new neurons as needed from stem and progenitor cells in its basal layers. In addition, there exists a mesenchymal‐like stem cell (MSC) located within the underlying lamina propria. Little is known about the function of this nasal MSC, or its relationship to the olfactory lineage, but there is considerable interest in using the nasal MSC for cell‐based therapies. We sought to further explore the biology of the nasal MSC by establishing neurosphere cultures from adult human nasal biopsies, and to examine the anatomic distribution of nasal MSCs. Methods: Nasal biopsies from human patients (n = 5) were obtained from superior, middle, and inferior turbinates or septum. Tissue was cultured to obtain nasal MSCs. Cultures were analyzed by immunocytochemistry and flow cytometry, as well as for differentiation capacity. Results: Although olfactory sensory neuroepithelium is restricted to superior regions in the nasal cavity, neurosphere‐forming MSC cultures were, surprisingly, obtained from olfactory as well as non‐olfactory regions. These MSC cultures exhibit characteristic robust neurosphere formation and express CD90, CD105, STRO‐1, and nestin. Nasal MSCs were found to give rise to neuronal‐like cells under differentiation conditions. Conclusion: The unanticipated broad anatomic distribution of nasal MSCs has implications for cell‐based therapy research.